PUBLIC ADMINISTRATION IN UKRAINE'S ENERGY SECTOR: CHALLENGES, PROBLEMS, AND APPROACHES TO THEIR SOLUTION (Coordinates of Public Administration, 2026)
The article provides a systematic analysis of public management issues in the energy sector of Ukraine under the current security, economic and institutional challenges. It is substantiated that the energy sector as a component of critical infrastructure plays a key role in ensuring economic stability, social equilibrium and national security of the state which leads to higher requirements for the effectiveness of its public management system. The essence and structural features of the energy management system are revealed, which integrates public-institutional, regulatory, financial-economic, technical-technological and security components. Based on the analysis of academic works by domestic and foreign re-searchers, as well as a summary of European experience in the functioning of energy markets, key systemic issues in the public management of the sector have been identified. These include institutional dysfunctions and the limited independence of the regulator, instability of the regulatory environment, financial and economic imbalances, a high level of security risks, as well as the complexity of implementing European norms and standards. Vertical and horizontal management imbalances have been revealed, which manifest themselves in inconsistencies between strategic planning and the practical implementation of policy, as well as between regulatory and budgetary and financial mechanisms. Particular attention has been paid to the impact of Russia’s full-scale war against Ukraine on the functioning of the domestic energy sector, which determines the need to integrate the security component into the strategic management system and enhance the sector’s resilience. Based on the research conducted, priority areas for improving public management have been substantiated, in particular the institutional strengthening of the regulator, the stabilization of regulatory policy, financial restructuring of energy markets, the development of digital management tools and the promotion of public-private partnerships. It has been proven that the implementation of the suggested approaches will contribute to improving the efficiency of the energy sector, strengthening energy security and accelerating Ukraine’s integration into the European energy space in the context of current transformational processes.